Health-related quality of life in patients with diabetic foot ulceration: study protocol for adaptation and validation of patient-reported outcome measurements (PROMs) in Dutch-speaking patients. Issue 12 (23rd December 2019) - Rezaie, Wahid; Lusendi, Flora; Doggen, Kris; Matricali, Giovanni; Nobels, Frank
Abstract : Introduction: Diabetic foot ulceration (DFU) is a common late-stage complication of diabetes with a large impact on health status and quality of life. Patient-reported outcome measures (PROMs) provide a standardised method of obtaining patients' views on their well-being. The DFU Scale Short Form (DFS-SF) is a validated disease-specific PROM for measuring health-related quality of life among DFU patients. The Lower Extremity Functional Scale (LEFS) is another PROM that can be used to measure physical functioning in patients with lower extremity disorders. The LEFS is not yet validated for DFU. Both instruments are not validated in the Dutch language. The purpose of this study is to culturally adapt and validate the DFS-SF and LEFS questionnaires for Belgian Dutch-speaking patients with DFU. Methods and analysis: This study will be conducted as a monocentre observational cohort study in DFU patients presenting at a hospital-based multidisciplinary diabetic foot clinic. Data will be collected from the medical electronic files and from DFS-SF, LEFS and five-level EuroQol five-dimension questionnaires that will be presented to the patients at defined time points. Reproducibility, internal consistency, floor and ceiling effects, construct validity and responsiveness will be assessed for the DFS-SF and LEFS. Ethics and dissemination: The study protocol has been approved by the Medical Ethics Committee of Onze-Lieve-Vrouw Hospital (Aalst, Belgium). The results of the study will be disseminated through peer-reviewed publications and conference presentations.